2017
DOI: 10.21307/jofnem-2017-079
|View full text |Cite
|
Sign up to set email alerts
|

A New Race (X12) of Soybean Cyst Nematode in China

Abstract: The soybean cyst nematode (SCN), Heterodera glycines, is a serious economic threat to soybean-producing regions worldwide. A new SCN population (called race X12) was detected in Shanxi province, China. Race X12 could reproduce on all the indicator lines of both race and Heterodera glycines (HG) type tests. The average number of females on Lee68 (susceptible control) was 171.40 with the lowest Female Index (FI) 61.31 on PI88788 and the highest FI 117.32 on Pickett in the race test. The average number of females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…SCN is estimated to cause annual yield losses of more than $1.2 billion in the United States (Koenning & Wrather, ) and more than $120 million in China (Wang, Zhao, & Chu, ). Moreover, increased virulence of SCN has been observed, and the dominant races appear to be shifting (Howland, Monnig, Mathesius, Nathan, & Mitchum, ; Hua et al, ; Lian et al, ). To some extent, this indicates that the ecological environment has caused evolution of nematode virulence, which is a serious threat to agro‐ecology and agricultural production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCN is estimated to cause annual yield losses of more than $1.2 billion in the United States (Koenning & Wrather, ) and more than $120 million in China (Wang, Zhao, & Chu, ). Moreover, increased virulence of SCN has been observed, and the dominant races appear to be shifting (Howland, Monnig, Mathesius, Nathan, & Mitchum, ; Hua et al, ; Lian et al, ). To some extent, this indicates that the ecological environment has caused evolution of nematode virulence, which is a serious threat to agro‐ecology and agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this race is able to successfully parasitize all resistant soybean germplasm tested, including the four indicator lines of the race scheme (Peking, Pickett, PI88788 and PI90763) (Riggs & Schmitt, ), the seven indicator lines of the HG type test (Peking, PI88788, PI90763, PI437654, PI 209332, PI 89772 and PI548316) (Niblack et al, ) and ZDD2315, the most promising elite resistant germplasm from China. Indeed, ZDD2315 is resistant to all SCN populations identified thus far, except for the newly identified race X12 (Lian et al, ). PI437654 is another elite resistant germplasm from the United States that is vulnerable to few natural SCN populations (Donald & Young, ; Jiao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a total of 10 SCN races were detected in China, of which races 1 and 3 are majorly distributed in soybean-producing areas in Northeast China, while race 4 is the dominant race over the Huanghuaihai Valley. Recently, a new race (X12) was identified in China (Lian et al 2017), which could infect all the tested soybean sources and showed a stronger virulence than race 4 (which had previously been thought the most virulent among all the SCN races). A 2nd population of race X12 was identified in Hekou Town, Gujiao City, Shanxi Province, China (Lian et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The major resistant cultivars, Kangxian series, originally bred for SCN race 3 resistance, does not have resistance to the newly identified races 4 and 14 in northeastern China (Hua et al., 2018). A new and super‐virulent race (X12) was found to be able to reproduce on all indicator lines for SCN race and HG Type identification in Shanxi Province in China (Lian et al., 2017). Similarly, SCN virulence shift resulting in resistance losses resulting from continuous planting of single‐source resistance in the same field is also common in the United States (Acharya et al., 2016; Hershman et al., 2008; Mitchum et al., 2007; Tylka & Mullaney, 2015; Vuong et al., 2010).…”
Section: Introductionmentioning
confidence: 99%